Polymorphisms within IGF1 and IGF1R Candidate genes in Gaolao Cattle Population - Wankhade, Aboli; Kale, Deepak; Singh, Jaya; Patil, Dinesh; Bonde, Sachin; Dhok, Atul; Bahiram, Krushna (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
IGF1 gene expresses during lactation, mediates galactopoietic effects, and regulates metabolism and growth and IGF1R gene relation with milk components. The objectives were to identify polymorphisms within IGF1 and IGF1R genes & find associations with milk traits. The blood was collected from 262 purebred cattle from the breeding tract, and test-day milk traits were recorded. PCR- SnaBI analysis of the 5′UTR region of the IGF1 gene revealed only BB genotype; however; IGFG1-SSCP screening of 5′UTR region of IGF1 gene revealed polymorphism with pattern A frequency as 0.685 and of B as 0.314 respectively. IGFG2 -TasI PCR-RFLP analysis of 5′UTR region of IGF1 gene revealed CC genotype. The monomorphic PCR-SSCP followed by sequencing revealed 14 computational SNPs. IGFRG5-TaqI PCR-RFLP within exon-21 region exhibited genetic variation at the locus. The IGFRG5 screening of the same exon 21 regions revealed two polymorphic SSCP patterns, which after direct sequencing revealed SNP A>G at 36th position. The findings will enrich IGF1 and IGFR candidate gene variation status and will aid in selecting and breeding decisions to improve Gaolao cattle.
Keywords: IGF1; IGF1R; Milk traits; Polymorphism; Zebu cattle